Spain : memorandum of interviews / Walter Citrine... Senor del Vayo - Citrine, Walter, 1887-1983
1937-10-11 016b-0044-001 PRIVATE & CONFIDENTIAL. MEMORANDUM OF INTERVIEW. Date 11th October, 1937. Time 3.15 to Reference WMC/FP/53 Present Sir Walter Citrine, Senor del Vayo. Mr. Middleton, Mr. Gillies. SUBJECT. SPAIN. On Monday, the 11th October, I received a telephone message from Mr. del Vayo, the Spanish government delegate at Geneva, asking could I see him that day, and I arranged an appointment accordingly for 3.15 the same afternoon. Mr. Middleton and Mr. Gillies were also present at this appointment. After discussing the general situation, Mr. del Vayo said he came with a specific request from the Government at Valencia that all help should be given by the British Government to evacuate from 50,000 to 60,000 of the miners and others in Asturia, who were fighting against Franco. Sooner or later Gijon would be taken by the rebels, and unless these men were evacuated there would be wholesale slaughter. He stated that he had seen Leon Blum, who had expressed his personal support for the evacuation, and that Blum would also support the request at the next meeting of the French Government. Blum had, however, pointed out the necessity of getting the support of the British Government. I at once pointed out to Mr. del Vayo that what was being pressed was the taking of 50,000 or 60,000 combatants, transporting them to France and sending them across France back into Republican Spain. This meant that the British Government would be asked, in effect, to send reinforcements to the Republican Army. France had already declined to receive any more refugees, and was evacuating existing refugees as rapidly as possible from French territory. Del Vayo agreed that the refugees could not stay in France and that they would have to be sent to Spain, but he said the alternative was that they would be slaughtered by Franco. There was no general refugee problem as such women and children as it was necessary to evacuate had already left Gijon. The Spanish Government would probably charter British ships for the purposes of evacuation, but they wanted the British and French Governments to give protection to these. After some further conversation, it was decided that I should try to see the Foreign Secretary. Mr. Eden, was however, at Balmoral and would not be back until Tuesday evening. I therefore arranged to see Lord Cranborne that afternoon at 5.15. 292/946/16b/48(i)